[PP.02.14] ANTIHYPERTENSIVE EFFECT OF LOSARTAN – ONE-YEAR FOLLOW-UP STUDY. (September 2017) - Stojanov, V.; Radivojevic, N.; Jakovljevic, B.
Abstract : Objective: The aim was to assess the efficiency and safety of losartan therapy in patients with stage I and stage II hypertension during a one-year follow-up period. Design and method: A cross-sectional study comprised 199 patients (100 men and 99 women) with stage I or stage II arterial hypertension, aged 60.9 ± 10.5 years. All patients were treated with a single daily dose of 50 mg losartan per os; the dose was increased to 5 mg after two weeks in persons who failed to decrease blood pressure adequately; the dose was increased to 100 mg if blood pressure was not regulated. Patients were followed up for one year. Blood pressure (BP) was measured by an oscillometric device at the beginning of the study, hemodynamic monitoring was performed using a thoracic bioelectric impedance method (Task Force monitor), and ambulatory blood pressure monitoring was performed by Space Labs 90202 device in all patients. The differences in selected parameters before and after the losartan therapy were tested with Student's t-test for paired samples. Results: Mean systolic blood pressure (SPB) at the beginning of the study was 163.8 mmHg; mean diastolic blood pressure (DBP) was 101.8 mmHg; mean heart rate was 74 beats/min. After therapy, mean SBP was significantly reduced to 137.1 mmHg (p < 0.001), DBP was significantly reduced to 88.9 mmHg (p < 0.001), and heart rate was 72 beats/min. At the beginning, mean % of vasoconstriction was 75 ± 15 among men, and 62 ± 13 among women. After one month of losartan therapy, mean % of vasoconstriction 38 ± 11 in men, and 34 ± 12 in women. At the end of the losartan treatment, mean % of vasoconstriction 10 ± 9 in men, and 9 ± 9 in women. The differences are highly statistically significant (all p < 0.001). At the end, 71% remained treated with 50 mg losartan, and only 29% of patients were treated with 100 mg losartan. Conclusions: One-year therapy with losartan is highly efficient in the regulation of blood pressure and in decreasing vasoconstriction in hypertensive patients.